Design and Characterization of Decellularized Caprine Liver Matrix Constructs for Liver Tissue Engineering - Supriya Bhatt; Jayanthi Krishnakumar; Kondepudi Lakshmi Mounica; Manasa Nune (Macromolecular Materials and Engineering)
Abstract This study focuses on developing and characterizing decellularized caprine liver scaffolds and their application in liver tissue engineering. Decellularization is achieved through chemical and enzymatic methods, effectively removing cellular components while preserving critical extracellular matrix (ECM) elements such as collagen and glycosaminoglycans (GAGs), as confirmed by histological and biochemical analyses. The scaffolds are further processed into hydrogels by combining decellularized liver matrix (dLM) with chitosan (CH) and polyvinyl alcohol (PVA), optimized through freeze‐thaw (FT) cross‐linking. Rheological studies show shear‐thinning behavior and enhanced mechanical properties in the crosslinked dLM hydrogels, making them suitable for bioprinting applications. Scanning electron microscopy (SEM) reveals a porous structure favorable to cell adhesion, nutrient diffusion, and vascularization. Biocompatibility is confirmed through live/dead and MTT assays, demonstrating higher cell viability and proliferation on crosslinked scaffolds. HepG2 cells cultured on these scaffolds express hepatic‐specific markers, such as Albumin and Cytokeratin‐18, and exhibit functional capabilities, including urea metabolism and albumin synthesis, highlighting the scaffold's ability to support liver‐specific activities. Collectively, these findings demonstrate the potential of FT crosslinked dLM‐based hydrogels as promising candidates for liver tissue engineering, providing a biomimetic microenvironment that supports cellular functionality and promotes tissue regeneration.